Development of a Multipurpose Hydro Environmental Tool using Swarms, UAV and USV - Rangel, Rodrigo Kuntz; Freitas, Joacy L. [UNESP]; Rodrigues, Vilmar Antonio [UNESP]; IEEE (Ieee, 2019)
This paper describe the development of a multipurpose hydro environmental tool to monitor the rivers and dams, and check the health of these places in terms of water quality and the level of siltation. In Brazil, the dams are used to supply water and generate electricity to the population. The monitoring of water resources is very important to check the degradation indices of the areas and maintain the health of rivers and reservoirs, in the actual days, the current monitoring process has been proved inefficient, due to the lack of financial resources in face of the size of the areas to be monitored. Our proposal is an alternative tool, using aerial (UAV) and aquatic (USV) drones, working together to get information about the water quality, depth of rivers and dams, and aerial pictures of these areas. The communication between the USV and aerial drone is performed in real time, and in automatic mode the quadcopter can follow the USV and control it. Due the dams size, more than one aerial drone or USV system can be used to mapping the areas, in this case the Swarm concept is applied to do the management of the drones. The use of both systems together will result in a complete map of these regions (surface and underwater), using a GIS software it is possible merge theses information in an unique muftilayer map that will be very useful to the authorities check the real health of our water resources in Brazil.